2014
DOI: 10.1039/c4sm00049h
|View full text |Cite
|
Sign up to set email alerts
|

Flow and jamming of granular suspensions in foams

Abstract: Abstract:The drainage of particulate foams is studied under conditions where the particles are not trapped individually by constrictions of the interstitial pore space. The drainage velocity decreases continuously as the particle volume fraction increases. The suspensions jam -and therefore drainage stops -for values which reveal a strong effect of the particle size.In accounting for the particular geometry of the foam, we show that accounts for unusual confinement effects when the particles pack into the foam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 28 publications
2
49
1
Order By: Relevance
“…In particular the ratio of the size of the particles to the size of the Plateau borders l is critical to determining how drainage proceeds. This ratio was named confinement parameter by O. Pitois and colleagues [14][15][16]30], and is a key parameter to know whether the particle suspension or the pure liquid flows. l is defined as:…”
Section: Drainage Of Aqueous Foamsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the ratio of the size of the particles to the size of the Plateau borders l is critical to determining how drainage proceeds. This ratio was named confinement parameter by O. Pitois and colleagues [14][15][16]30], and is a key parameter to know whether the particle suspension or the pure liquid flows. l is defined as:…”
Section: Drainage Of Aqueous Foamsmentioning
confidence: 99%
“…There exists a number of studies, where foam drainage is studied in the presence of solid particles. In the case of solid particles, Pitois and co-workers have also shown that how the drainage proceeds depends strongly on the ratio of the particle size to the foam channel size [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the foam regime transition in aqueous foams is usually caused by a change in the surface viscosity or interface mobility [186,187]. However, it is difficult to make the same claim in foams containing nanoparticles because the presence of hydrophilic solid particles can change the interfacial properties to only a small extent [180].To explain the foam drainage behaviors in the presence of hydrophilic particles, several mechanisms have been proposed, such as rheology of the powder suspension and clogging in the confined regions of the Plateau borders [172,178,181,[183][184][185]. Among them, the most important parameter controlling the drainage behaviors of foams with hydrophilic particles is the confinement parameter, , which relates the size of the particle to the maximum diameter of the circle inscribed in the Plateau border cross-section.…”
mentioning
confidence: 99%
“…To explain the foam drainage behaviors in the presence of hydrophilic particles, several mechanisms have been proposed, such as rheology of the powder suspension and clogging in the confined regions of the Plateau borders [172,178,181,[183][184][185]. Among them, the most important parameter controlling the drainage behaviors of foams with hydrophilic particles is the confinement parameter, , which relates the size of the particle to the maximum diameter of the circle inscribed in the Plateau border cross-section.…”
mentioning
confidence: 99%
See 1 more Smart Citation